Tyrosine receptor kinase B is a drug target in astrocytomas. Issue 1 (10th July 2016) - Ni, Jing; Xie, Shaozhen; Ramkissoon, Shakti H.; Luu, Victor; Sun, Yu; Bandopadhayay, Pratiti; Beroukhim, Rameen; Roberts, Thomas M.; Stiles, Charles D.; Segal, Rosalind A.; Ligon, Keith L.; Hahn, William C.; et al.
Abstract: Background: Astrocytomas are the most common primary human brain tumors. Receptor tyrosine kinases (RTKs), including tyrosine receptor kinase B (TrkB, also known as tropomyosin-related kinase B; encoded by neurotrophic tyrosine kinase receptor type 2 [ NTRK2 ]), are frequently mutated by rearrangement/fusion in high-grade and low-grade astrocytomas. We found that activated TrkB can contribute to the development of astrocytoma and might serve as a therapeutic target in this tumor type. Methods: To identify RTKs capable of inducing astrocytoma formation, a library of human tyrosine kinases was screened for the ability to transform murine Ink4a −/− /Arf −/− astrocytes. Orthotopic allograft studies were conducted to evaluate the effects of RTKs on the development of astrocytoma. Since TrkB was identified as a driver of astrocytoma formation, the effect of the Trk inhibitors AZD1480 and RXDX-101 was assessed in astrocytoma cells expressing activated TrkB. RNA sequencing, real-time PCR, western blotting, and enzyme-linked immunosorbent assays were conducted to characterize NTRK2 in astrocytomas. Results: Activated TrkB cooperated with Ink4a/Arf loss to induce the formation of astrocytomas through a mechanism mediated by activation of signal transducer and activator of transcription 3 (STAT3). TrkB activation positively correlated with Ccl2 expression. TrkB-induced astrocytomas remained dependent on TrkB signaling for survival, highlighting a role of NTRK2 as an addictive oncogene. Furthermore, the QKI-NTRK2 fusion associated with human astrocytoma transformed Ink4a −/− /Arf −/− astrocytes, and this process was also mediated via STAT3 signaling. Conclusions: Our findings provide evidence that constitutively activated NTRK2 alleles, notably the human tumor-associated QKI-NTRK2 fusion, can cooperate with Ink4a/Arf loss to drive astrocytoma formation. Therefore, we propose NTRK2 as a potential therapeutic target in the subset of astrocytoma patients defined by QKI-NTRK2 fusion.